Tuinen Tonen 2: vanuit een andere hoek : kunstproject in Boom van 13 augustus tot 11 september 1994. - Kenis, Jef; Boom (Turnhout : de oorzaak & zn., 1994)
Peters, Willy ; Brusselmans, Luc ; Debie, Annie ; Pellens, Lucas ; Custers, Stefan ; Clinckx, Christine ; Daled, Jeroen ; Cordenier, Marc ; Merckaert, Patrick ; Massart, Jean-Georges ; Van Breedam, Camiel ; Vervoort, Carla ; Moszowski, Wladimir.
Boom, 13 augustus tot 11 september 1994
kunstcatalogus